Plant biotechnology 4.0: an approach to “Speed Breeding” (Research, Society and Development, 2021)
The increase in human population related to food demand and the current climate change scenario have challenged researchers around the world, making it essential to optimize the obtainment of cultivars with high productivity, combined with higher nutritional quality and greater resistance to abiotic and biotic conditions, prioritizing the sustainability and the preservation of natural resources. In this context, plant breeding associated with biotechnology techniques makes it possible to genetically modify plants for human benefit, in order to solve problems and create products that meet the desirable agronomic traits, however, the development of new cultivars requires a long period to select superior strains with high agronomic performance. To reduce the cycle in classic breeding programs, some techniques are being used and show promising results, one of them is Speed ​​Breeding, which reduces the breeding time and speeds up research by obtaining new generations quickly, through the use of controlled light and temperature conditions to increase plant growth, accelerating the search for cultivars that meet the needs of producers and consumers. This work aims to present, through a critical approach, the Speed ​​Breeding methodology as a tool to accelerate plant breeding programs.